Nitrogen sources and its uptake in Dendrobium Orchid by15N tracer study - S. Ruamrungsri (2018)
Orchid growers apply a large amount of fertilizer to promote growth and flower quality via both foliar and root spray. However, the efficiency of nutrient uptake via roots or leaves was rarely reported. Two experiments were carried out to study the appropriate source of N (NH4and/or NO3) for Dendrobium and to compare NH4+and NO3-uptake via roots and leaves. In the first experiment, 6-month-old Dendrobium Sonia 'Ear Sakul' plants were supplied with different of NH4+:NO3-ratios (0:0, 0:200, 50:150 and 100:100 mg N L-1) once a week. The results showed that the number of florets/spike, the length of spike and flowering percentage increased when the ratio of NH4increased. In the second experiment, 6-month-old Dendrobium Sonia 'Ear Sakul' were transplanted into the new pots using small bricks as growing media. The15N tracer was fed to plant with 20 ml of different labeled-N sources. Plants were fed via leaves or roots. The nitrogen was applied as 1) 5.0 mM of15NH4+, 2) 2.5 mM of15NH4+plus 2.5 mM of NO3-, 3) 5.0 mM of15NO3-and 4) 2.5 mM of NH4+plus 2.5 mM of15NO3-, at 1, 3 and 6 d. The results showed that Dendrobium prefer the combination form of N since the15N uptake was higher in combination of NH4-N with NO3-N, especially when feeding via leaves. Presence of NO3in the solution increased the absorption of NH4compared to feeding with NH4alone. Supply N-fertilizer in the combination of NH4:NO3at 100:100 mg N via leaves was recommended to stimulate growth and the uptake of ion into plant organs for assimilation.